(untitled) (Perner’s Contacts, 2010)
The paper is devoted to the modelling of shunting slope operation using the queueing theory. Studied process is modelled as an unreliable queueing system with costumer service completing after breakdown occurence. The paper introduces two different models – a mathematical model and an simulation model created by using software Witness. In the end of the paper comparison of reached outcomes is carried out.